2004
DOI: 10.1590/s1516-635x2004000200003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of energy levels of diets formulated on total or digestible amino acid basis on broiler performance

Abstract: This study was conducted to evaluate the performance and carcass and breast yields of broilers fed two different energy levels (3,200 or 2,900 kcal ME/kg) and two ways of expressing amino acid requirements (total TAA or digestible DAA) between 21 and 42 days of age. The results showed that broilers fed the diet containing 3,200 kcal ME/kg had higher weight gain (P=0.015), better feed conversion (P=0.001), and higher abdominal fat deposition (P=0.001) as compared to those fed the diet containing 2,900 kcal ME/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 9 publications
3
9
0
2
Order By: Relevance
“…These results are in consistent with the findings of Maiorka et al (2004) and Fernandez et al (1995) who reported that feed efficiency was improved in broilers fed diets formulated on DAA than TAA basis. Improved feed efficiency in DAA fed birds is due to more balanced nutrients, absorption and protein synthesis which was influenced by the diet formulated based on DAA (Khaksar and Golian, 2009).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are in consistent with the findings of Maiorka et al (2004) and Fernandez et al (1995) who reported that feed efficiency was improved in broilers fed diets formulated on DAA than TAA basis. Improved feed efficiency in DAA fed birds is due to more balanced nutrients, absorption and protein synthesis which was influenced by the diet formulated based on DAA (Khaksar and Golian, 2009).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, recent interest in poultry feed formulation has led to take into account the digestible amino acids rather than total (Khaksar and Golian, 2009). In this regard, there have been a number of papers demonstrating the advantages of using digestible rather than total amino acids to formulate broiler diets (Maiorka et al, 2004(Maiorka et al, , 2005Farrell et al, 1999). However, no reports on the interaction between this method of amino acid formulation and the use of soybean oil with dietary bile salts found in broiler chickens.…”
Section: Introductionmentioning
confidence: 99%
“…The improvement in response to dietary energy during the starter phase were further shown by the reports of Maiorka et al (2004) who observed improved body weight and FCR with increased dietary energy in the starter period. The present result disagrees the reports of Nguyen and Bunchasak (2005) The economic evaluation shows that the mean feed cost necessary to produce a kg of body weight is significantly (P<0.05) lower in D1 as compared to D0, D2 and D3.…”
Section: Discussionmentioning
confidence: 61%
“…Nevertheless, based on its influence on feed intake, excessive dietary energy supply may limit nutrients intake (e.g. amino acids) and consequently compromise bird performance (Maiorka et al, 2004). In the current study, increasing in dietary AMEn decreased protein and lysine intake, which might explain the quadratic responses observed on FBW and WG.…”
Section: Resultsmentioning
confidence: 99%